Advanced drug delivery systems can assist in managing influenza virus infection: A hypothesis. (November 2020) - Chan, Yinghan; Ng, Sin Wi; Mehta, Meenu; Anand, Krishnan; Kumar Singh, Sachin; Gupta, Gaurav; Chellappan, Dinesh Kumar; Dua, Kamal
Abstract: Outbreaks of influenza infections in the past have severely impacted global health and socioeconomic growth. Antivirals and vaccines are remarkable medical innovations that have been successful in reducing the rates of morbidity and mortality from this disease. However, the relentless emergence of drug resistance has led to a worrisome increase in the trend of influenza outbreaks, characterized by worsened clinical outcomes as well as increased economic burden. This has prompted the need for breakthrough innovations that can effectively manage influenza outbreaks. This article provides an insight into a novel hypothesis that describes how the integration of nanomedicine, with the development of drugs and vaccines can potentially enhance body immune response and the efficacies of anti-viral therapeutics to combat influenza infections.